Uterus transplantation: current progress and future prospects - Johannesson L; Järvholm S (Dove Medical Press, 2016)
Liza Johannesson, Stina Järvholm Department of Obstetrics and Gynecology, Sahlgrenska Academy, University of Gothenburg, Sahlgrenska University Hospital, Gothenburg, Sweden Abstract: Even if reproductive medicine has been remarkably successful during the past few decades, with the introduction of in vitro fertilization in the late 1970s and intracytoplasmic sperm injection in the early 1990s, it has been repeatedly mocked by infertility due to an absolute uterine factor. No treatment has been available for the women suffering from an absent or dysfunctional uterus, in terms of carrying a pregnancy. Approximately one in 500 women suffer from absolute uterine infertility, and the option so far to become a mother has been to either adopt or utilize gestational surrogacy. As of today, a total of eleven cases of human uterus transplantations have been reported worldwide, conducted in three different countries. The results of these initial experimental cases far exceed what might be expected of a novel surgical method. Many more uterus transplantations are to be expected in the near future, as other research teams’ preparations are being ready to be put into clinical practice. In this review, we summarize the current worldwide experience of uterus transplantation as a treatment of absolute uterine factor infertility and the future prospects of human uterus transplantation. Keywords: uterus, transplantation, infertility